LAJU SERANGAN KUMBANG AMBROSIA XYLEBORUS SP. PADA DOLOK TUSAM (PINUS MERKUSII) - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1994)
The effect af  some treatments of  freshly cut Sumaura  pine logs (Pinus merkusii) on the rate of ambrosia  beetle attack  (Xylebarus sp.)  was observed. The results showed that:l . Most of the tested  logs were initially infested by the beetles about one week after felling.2.There was  no significant difference among the susceptibility of any sections of  the tree trumk,  whether they were teaken from  the bottom,  middle or top portions.3. Debarked logs were more  susceptible, at least in the first week. to the beetle attack.4. Keeping the logs in the shady areas. and  also sprinkling with water, may lengthen the period  of  Jog freshness, but it  also means praviding  suitable host  for  the beetles continuausly.